Semaphorin 7A as a potential immune regulator and promising therapeutic target in rheumatoid arthritis. Issue 1 (December 2017) - Xie, Jianmin; Wang, Hao
Abstract Background Semaphorin 7A (Sema7A) is expressed by several different classes of lymphoid and myeloid cells and is a potent immunomodulator. We examined the role of Sema7A in modulating cellular immune responses and to provide experimental data validating the therapeutic potential of Sema7A in rheumatoid arthritis (RA). Methods Soluble Sema7A (sSema7A) levels in the serum and synovial fluid from patients with RA or osteoarthritis, as well as cytokine secretions, were analyzed with an enzyme-linked immunosorbent assay. The cell surface levels and transcripts of Sema7A were evaluated in T cells and monocytes from patients with RA. The effect of Sema7A on the functions of primary T cells isolated from the peripheral blood of healthy donors was observed. Detection of the activation of the signal mediator focal adhesion kinase was performed by Western blotting. Shedding of sSema7A was evaluated in monocytes. The introduction of anti-Sema7A antibody to mice with collagen-induced arthritis (CIA) was observed in vivo. Results Upregulation of sSema7A levels in both the serum and synovial fluid of patients with RA was correlated with disease activity markers. sSema7A markedly increased Th1/Th17 cytokine secretion and induced evident upregulation of T-bet and retinoic acid receptor-related orphan nuclear receptor γt levels in T cells. Cell surface Sema7A was cleaved by a disintegrin and metalloprotease 17 (ADAM17) in monocytes. Interleukin-6 and tumor necrosis factor-α stimulated ADAM17 secretion in synovial macrophages. Blocking of β1-integrin abrogated the Sema7A-mediated cytokine secretion. Treatment with an anti-Sema7A antibody significantly attenuated CIA. Conclusions These findings indicate that Sema7A as a potent activator of T cells and monocytes in the immune response contributes to the inflammation and progression of RA, suggesting its therapeutic potential in the treatment of RA.